Portrait of an English migration : North Yorkshire people in North America - Van Vugt, William E., 1957- (McGill-Queen's transatlantic studies, 2021)
"Portrait of an English Migration recounts the history of those who left North Yorkshire for North America between the eighteenth century and the early twentieth century. Focusing on individual stories of migrants and their families, this book provides many personal glimpses of the migration experience of those who left England's largest county to build new lives in the United States and Canada. Exploring the local history, geography, and cultures of Yorkshire and the key places of settlement in North America, William Van Vugt deepens our understanding of the historic migration process: how local conditions and access to information influenced migration decisions, the role of local networks in migration patterns, and the significance of family connections, religious identities, and land ownership to the migrants themselves. He considers the extent to which English migrants shaped regional culture and contributed to economic development, addressing ongoing questions about identity and what it meant to be English in North America. Full of first-person accounts and stories from migrants themselves, Portrait of an English Migration is both a sweeping history of two centuries of migration and an intimate look at the lives of generations of Yorkshire people who crossed the ocean to make a new home."--